Politique publique et action collective territoriale. Une analyse de la politique environnement-emploi de la Région Nord-Pas de Calais - Muriel Maillefert; Nicola Screnci (Développement Durable et Territoires)
This paper examines a special public policy plan put into place in the Nord-Pas de Calais Region between 1993 and 2002. This plan called Employment-Environment Policy mixed the territorial and the local collective action dimensions. Examination of the ethos for collective action put forth by the various participants shows that the main difficulty for implementation arose, not from the very objectives of the programme that were in harmony with the Region's ones, but rather from the kinds of collective actions developed by the various players involved in the plan.